2015
DOI: 10.4317/jced.51876
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro evaluation of the effect of sandblasting and laser surface treatment on the shear bond strength of a composite resin to the facial surface of primary anterior stainless steel crowns

Abstract: Objectives: The present study was conducted to evaluate the optimal method of enhancing the bond strength of a composite resin to the facial surface of the primary anterior stainless steel crowns using various surface treatments namely Nd: YAG laser surface treatment, sandblasting , alloy primer application and no surface treatment. Study Design: The study sample consisted of 60 primary anterior stainless steel crowns (UnitekTM size R 4), with 15 samples randomly divided into the 4 study groups, embedded in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Actually, many studies have shown that metalresin bonding is generally affected by surface treatments of the bonding area and adhesive systems (13)(14)(15)(16)(17). To enhance metal-resin bonding, retention beads are frequently used and are suggested in metal-resin restorations, but macromechanical retention devices have many disadvantages, such as causing an overcontoured resin veneered restoration or an unpleasing esthetic result caused by reverberating of the retention beads under the composite veneer (13,16,18). In this study, no macro-mechanical retention devices were used because the aim of this study was to assess and compare showed that metal substructures with retention devices fabricated by laser sintering (DMLS) had higher SBS values than those fabricated by casting, while there were no statistical differences between the two techniques when the metal specimens were prepared without retention devices (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, many studies have shown that metalresin bonding is generally affected by surface treatments of the bonding area and adhesive systems (13)(14)(15)(16)(17). To enhance metal-resin bonding, retention beads are frequently used and are suggested in metal-resin restorations, but macromechanical retention devices have many disadvantages, such as causing an overcontoured resin veneered restoration or an unpleasing esthetic result caused by reverberating of the retention beads under the composite veneer (13,16,18). In this study, no macro-mechanical retention devices were used because the aim of this study was to assess and compare showed that metal substructures with retention devices fabricated by laser sintering (DMLS) had higher SBS values than those fabricated by casting, while there were no statistical differences between the two techniques when the metal specimens were prepared without retention devices (18).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the results of the present study, there were no significant differences between the casting and the DMLS groups. Generally, SBS tests are used for evaluating bonding strengths in in-vitro studies, as the shear forces simulate the occlusal contact forces in the masticatory system (13)(14)(15)(16)(17); (20)(21)(22). As previous studies have revealed, the surface characteristics of the bonding area affects the SBS values (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…16,21,10 Bond strength can be improved by the presence of micromechanical retention, as the creation of roughened metal surfaces may allow ceromer to penetrate into pits and fissures, thereby creating a stronger micromechanical interlock. The roughness of metal surface changes in accordance with the several characteristics of metal and applied FIG.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Surface treatments increase the available surface for adhesion; however, the application of every routine method has advantages and disadvantages in several types of metal infrastructures, and there is a need for more adjusted and predictable surface changes. Currently available treatments provide variable success after their application to the several types of dental materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation